2016
DOI: 10.1007/s11336-016-9512-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Robustness Study of the Polychoric Correlation Estimation

Abstract: Asymptotic robustness against misspecification of the underlying distribution for the polychoric correlation estimation is studied. The asymptotic normality of the pseudo-maximum likelihood estimator is derived using the two-step estimation procedure. The t distribution assumption and the skew-normal distribution assumption are used as alternatives to the normal distribution assumption in a numerical study. The numerical results show that the underlying normal distribution can be substantially biased, even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…Furthermore, McDonald's ordinal omega and the greatest lower bound to reliability were assessed [41][42][43]. Inter-item and item-total correlations were measured by polychoric correlations and Spearman's rho coefficients [44][45][46]. The normality of the data distribution was assessed by the Kolmogorov-Smirnov (Lilliefors) test.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, McDonald's ordinal omega and the greatest lower bound to reliability were assessed [41][42][43]. Inter-item and item-total correlations were measured by polychoric correlations and Spearman's rho coefficients [44][45][46]. The normality of the data distribution was assessed by the Kolmogorov-Smirnov (Lilliefors) test.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the latent normality assumption has often been taken for granted by applied researchers (Foldnes and Grønneberg, 2020). If there are violations of latent normality, parameter estimates based on the incorrect latent normality assumption can provide substantially biased estimates (Jin and Yang-Wallentin, 2017;Foldnes and Grønneberg, 2020). It has shown that the latent normality assumption can be empirically tested (Maydeu-Olivares et al, 2009;Raykov and Marcoulides, 2015;Foldnes and Grønneberg, 2020).…”
Section: The Normality Assumption and The Latent Normality Assumptionmentioning
confidence: 99%
“…If the ordinal nature of variables would be taken seriously, more sophisticated modeling strategies for factor analysis that try to estimate more flexible distributions are required (Jin and Yang-Wallentin, 2017;Foldnes and Grønneberg, 2019). A particularly attractive distribution class is the factor copula model (Krupskii and Joe, 2013;Nikoloulopoulos and Joe, 2015;Ackerer and Vatter, 2017;Krupskii and Genton, 2018).…”
Section: The Normality Assumption and The Latent Normality Assumptionmentioning
confidence: 99%
“…5 , the relationship between and is displayed for the ordinalized bivariate Student’s t . The reader can also refer to Jin and Yang-Wallentin ( 2017 ) for some potential alternatives to the bivariate normal distribution assumption as un underlying stochastic model for ordinal data, where the authors study robustness against misspecification of the underlying distribution with respect to the polychoric correlation estimation.
Fig.
…”
Section: Conclusion and Further Researchmentioning
confidence: 99%